2021
DOI: 10.3390/ijms222111315
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Modulation in p53 Signaling Pathway by Flavonoids: A Potential Strategy towards the Treatment of Cancer

Abstract: Cancer is a major cause of death, affecting human life in both developed and developing countries. Numerous antitumor agents exist but their toxicity and low efficacy limits their utility. Furthermore, the complex pathophysiological mechanisms of cancer, serious side effects and poor prognosis restrict the administration of available cancer therapies. Thus, developing novel therapeutic agents are required towards a simultaneous targeting of major dysregulated signaling mediators in cancer etiology, while posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 114 publications
0
12
0
Order By: Relevance
“…p53 signaling pathway is a significant apoptotic target in many cancer types. It has been proved that activation of p53 signaling pathway can control proliferation and trigger apoptosis of HCC cells [ 41 , 42 ]. Furthermore, estrogen signaling pathway was reported to protect the occurrence and development of HCC.…”
Section: Resultsmentioning
confidence: 99%
“…p53 signaling pathway is a significant apoptotic target in many cancer types. It has been proved that activation of p53 signaling pathway can control proliferation and trigger apoptosis of HCC cells [ 41 , 42 ]. Furthermore, estrogen signaling pathway was reported to protect the occurrence and development of HCC.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, as the RiskScore changed, the pathways involved in tumor occurrence and progression were different. For example, we found that among the higher-scored pathways, the enrichment score of pathways such as P53 signaling pathway ( 71 ) increased with the increase of RiskScore, while the enrichment score of metabolic pathways such as fatty acid metabolism ( 72 ), glycolysis gluconeogenesis ( 73 ), galactose metabolism ( 74 ) decreased with the increase of RiskScore. Previous literature reports have shown that these pathways are all involved in tumor progression, but they may play different roles in different tumors, and this also requires follow-up research for verification.…”
Section: Discussionmentioning
confidence: 99%
“…The former includes B-cell lymphoma-extra-large (Bcl-xL), Bcl-2, and myeloid-cell leukemia 1 (Mcl-1), while the latter includes Bcl-2-associated X protein (Bax), Bcl-2 homologous antagonist/killer (Bak), and BH3. Bak and Bax enhance the formation of MAC, while Mcl-1, Bcl-2, and Bcl-xL inhibit its formation ( 34 ). Apart from the established roles of Bak and Bax in apoptosis, the ratio of pro-apoptotic/anti-apoptotic proteins is what governs apoptosis, rather than individual protein expression.…”
Section: Resistance Mechanisms In Cancer Chemotherapymentioning
confidence: 99%